2015
DOI: 10.1126/sciadv.1500248
|View full text |Cite
|
Sign up to set email alerts
|

A Candida albicans CRISPR system permits genetic engineering of essential genes and gene families

Abstract: Candida albicans is a pathogenic yeast that causes mucosal and systematic infections with high mortality. The absence of facile molecular genetics has been a major impediment to analysis of pathogenesis. The lack of meiosis coupled with the absence of plasmids makes genetic engineering cumbersome, especially for essential functions and gene families. We describe a C. albicans CRISPR system that overcomes many of the obstacles to genetic engineering in this organism. The high frequency with which CRISPR-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
388
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(395 citation statements)
references
References 29 publications
4
388
1
2
Order By: Relevance
“…Ume6 guide RNA primers (Ume6 Guide 2 fr and rv) were subcloned into pv1093 as previously described (Vyas et al 2015). Repair templates were made by PCR using indicated primer pairs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ume6 guide RNA primers (Ume6 Guide 2 fr and rv) were subcloned into pv1093 as previously described (Vyas et al 2015). Repair templates were made by PCR using indicated primer pairs.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, plasmids are not maintained consistently in C. albicans. The development of the Candida CRISPR system however has made introduction of mutations into the genome more efficient (Vyas et al 2015;Vyas et al 2018). During CRISPR-mediated genome editing, Cas9 nuclease bound to a guide RNA molecule targets a specific genomic sequence to be modified using base pairing.…”
Section: Introductionmentioning
confidence: 99%
“…Now CRISPR is making it possible to edit genes in many more organisms. In April, for example, researchers at the Whitehead Institute for Biomedical Research in Cambridge, Massachusetts, reported using CRISPR to study Candida albicans, a fungus that is particularly deadly in people with weakened immune systems, but had been difficult to genetically manipulate in the lab 3 . Jennifer Doudna, a CRISPR pioneer at the University of California, Berkeley, is keeping a list of CRISPR-altered creatures.…”
Section: Research Revolutionmentioning
confidence: 99%
“…These features make the CRISPR/Cas9 system quite simple and easy to design, as well as being highly effective, as proven in human [38] and mouse [39] cells. Following successful site-directed mutagenesis in mammalian cells, the CRISPR/Cas9 system has been used widely in a variety organisms from bacteria to higher eukaryotes: Candida albicans [41], Caenorhabditis elegans [42], fruit fly [43], zebrafish [44], rodents [45], and cattle [46].…”
Section: Molecular Breeding: Genomics and Genetic Engineering In Woodmentioning
confidence: 99%